Identification of Multiple Phytotoxins Produced by Fusarium virguliforme Including a Phytotoxic Effector (FvNIS1) Associated With Sudden Death Syndrome Foliar Symptoms - Chang, Hao-Xun; Domier, Leslie L.; Radwan, Osman; Yendrek, Craig R.; Hudson, Matthew E.; Hartman, Glen L. (Molecular plant-microbe interactions, 2016)
Sudden death syndrome (SDS) of soybean is caused by a soilborne pathogen, Fusarium virguliforme. Phytotoxins produced by F. virguliforme are translocated from infected roots to leaves, in which they cause SDS foliar symptoms. In this study, additional putative phytotoxins of F. virguliforme were identified, including three secondary metabolites and 11 effectors. While citrinin, fusaric acid, and radicicol induced foliar chlorosis and wilting, Soybean mosaic virus (SMV)-mediated overexpression of F. virguliforme necrosis-inducing secreted protein 1 (FvNIS1) induced SDS foliar symptoms that mimicked the development of foliar symptoms in the field. The expression level of fvnis1 remained steady over time, although foliar symptoms were delayed compared with the expression levels. SMV::FvNIS1 also displayed genotype-specific toxicity to which 75 of 80 soybean cultivars were susceptible. Genome-wide association mapping further identified three single nucleotide polymorphisms at two loci, where three leucine-rich repeat receptor-like protein kinase (LRR-RLK) genes were found. Culture filtrates of fvnis1 knockout mutants displayed a mild reduction in phytotoxicity, indicating that FvNIS1 is one of the phytotoxins responsible for SDS foliar symptoms and may contribute to the quantitative susceptibility of soybean by interacting with the LRR-RLK genes.